A NURSING REHABILITATION PROGRAM TO IMPROVE THE QUALITY OF LIFE OF PATIENTS WITH MENINGIOMA: A NARRATIVE REVIEW - Amelia Ganefianty; Sri Yona (Belitung Nursing Journal, 2019)
Meningioma is the most common type of primary brain tumor, which affect several domains of life, such as physiological, psychological, and social life conditions. Although surgery has been performed on meningioma patients in Indonesia, some patients still experience sequelae such as headache, impaired mobilization, disruption of activity, and visual disturbances. This narrative review aims to describe nursing rehabilitation programs in patients with meningioma in Indonesia. As a result, the nursing rehabilitation program is considered as an integral part of multidisciplinary rehabilitation, which can be applied in the nursing rehabilitation center and in the form of telenursing. The roles of nurses include providing evidence-based direct care, psychosocial support, patient / family education, care coordination, and continuing health promotion starting from the period of patient care in the hospital to discharge. In conclusion, the nursing rehabilitation program has the potential to improve the quality of life in meningioma patients, especially in Indonesia.